Repositioning the Old Fungicide Ciclopirox for New Medical Uses - Shen, Tao; Huang, Shile (Current Pharmaceutical Design, 2016)
Background: Ciclopirox (CPX) has been used as an antifungal agent in various formulations to treat superficial fungal infection for decades. Its effectiveness and safety in treatments have been demonstrated by multiple studies. Methods: Here we briefly summarize the pharmacological and toxicological properties of CPX as an antifungal agent, the new medical uses of CPX, as well as the correspondent molecular mechanisms. Results: Increasing evidence has demonstrated that CPX is able to inhibit tumor growth, ameliorate diabetes and its complications, prevent human immunodeficiency virus (HIV) infection, and improve age-associated cardiovascular defects. Interestingly, its antifungal activity and all those newly observed effects are more or less related to its capability of chelating iron and interfering with the related signaling pathways. Mechanistically, CPX is capable of modulating the activities of certain enzymes or signaling pathways, such as ribonucleotide reductase (RR), deoxyhypusine hydroxylase (DOHH)/eukaryotic translation initiation factor 5A (eIF5A), Wnt/ β-catenin, hypoxia-inducible factor-1α (HIF-1 α)/vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor 3 (VEGFR-3)/extracellular signal-regulated protein kinases 1/2, mammalian target of rapamycin, and cyclin dependent kinases (CDKs). Most of these activities are related to its chelation of iron. Conclusion: CPX, as an antifungal agent, may be repositioned for treatment of cancer and other human diseases.
Keywords: cancer